2020
DOI: 10.1111/jgh.14999
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diagnostic accuracy, technical success and adverse events of endoscopic ultrasound‐guided fine‐needle biopsy: A systematic review and meta‐analysis

Abstract: Background and AimEndoscopic ultrasound‐guided fine‐needle biopsy (EUS‐FNB) is used to diagnose lesions within or adjacent to the digestive tract. However, there is no report on the overall diagnostic accuracy, technical success, and adverse events of FNB. The aims of this study were to conduct a systematic review and meta‐analysis to comprehensively assess the diagnostic accuracy, technical success, and adverse events of FNB.MethodsPubmed, Embase, and Cochrane Library databases were searched for relevant arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…However, a previous meta-analysis discovered that 22 G needles were a predictor related to a higher diagnostic yield than 19, 20, and 25 G needles. 36 This discrepancy may be attributed to the targeted objects, as other studies included all the lesions around the digestive tract, while our study only included SELs. One of our included studies showed that 22 G needles and 25 G needles both had relatively high diagnostic yields (89% and 86%, respectively).…”
Section: Discussionmentioning
confidence: 87%
“…However, a previous meta-analysis discovered that 22 G needles were a predictor related to a higher diagnostic yield than 19, 20, and 25 G needles. 36 This discrepancy may be attributed to the targeted objects, as other studies included all the lesions around the digestive tract, while our study only included SELs. One of our included studies showed that 22 G needles and 25 G needles both had relatively high diagnostic yields (89% and 86%, respectively).…”
Section: Discussionmentioning
confidence: 87%
“…The incidence of haemorrhage following endoscopic ultrasound (EUS)-guided sampling has been analysed in several systematic reviews; the figure per thousand was 1.28 for EUS-guided with fine-needle aspiration (FNA) (51 studies, 10 941 patients), 123 5.81 for EUS-fine needle biopsy (FNB) (51 studies, 5330 patients) 124 and 6.63 for EUS-FNA of pancreatic cystic lesions (40 studies, 5124 patients). 125 Four studies reported on haemorrhage following EUS-guided sampling in patients prescribed antithrombotic agents.…”
Section: Endoscopic Ultrasound-guided With Fine-needle Aspiration and Other Interventionsmentioning
confidence: 99%
“…The incidence of haemorrhage following EUS-guided sampling has been analysed in several systematic reviews; the figure per thousand was 1.28 for EUS-FNA (51 studies, 10,941 patients) 123 , 5.81 for EUS-fine needle biopsy (FNB) (51 studies, 5,330 patients) 124 and 6.63 for EUS-FNA of pancreatic cystic lesions (40 studies, 5,124 patients) 125 . Four studies reported on haemorrhage following EUS-guided sampling in patients prescribed antithrombotic agents 126 127 128 129 .…”
Section: Endoscopic Proceduresmentioning
confidence: 99%